Bleomycin administered by laser-assisted drug delivery or intradermal needle-injection results in distinct biodistribution patterns in skin: in vivo investigations with mass spectrometry imaging. (1st January 2021) - Hendel, Kristoffer; Hansen, Anders C. N.; Bik, Liora; Bagger, Charlotte; van Doorn, Martijn B. A.; Janfelt, Christian; Olesen, Uffe H.; Haedersdal, Merete; Lerche, Catharina M.
Abstract: Bleomycin (BLM) is being repositioned in dermato-oncology for intralesional and intra-tumoural use. Although conventionally administered by local needle injections (NIs), ablative fractional lasers (AFLs) can facilitate topical BLM delivery. Adding local electroporation (EP) can augment intracellular uptake in the target tissue. Here, we characterize and compare BLM biodistribution patterns, cutaneous pharmacokinetic profiles, and tolerability in an in vivo pig model following fractional laser-assisted topical drug delivery and intradermal NI, with and without subsequent EP. In vivo pig skin was treated with AFL and topical BLM or NI with BLM, alone or with additional EP, and followed for 1, 2 and 4 h and eventually up to 9 d. BLM biodistribution was assessed by spatiotemporal mass spectrometry imaging. Cutaneous pharmacokinetics were assessed by mass spectrometry quantification and temporal imaging. Tolerability was evaluated by local skin reactions (LSRs) and skin integrity measurements. AFL and NI resulted in distinct BLM biodistributions: AFL resulted in a horizontal belt-shaped BLM distribution along the skin surface, and NI resulted in BLM radiating from the injection site. Cutaneous pharmacokinetic analyses and temporal imaging showed a substantial reduction in BLM concentration within the first few hours following administration. LSRs were tolerable overall, and all interventions permitted almost complete recovery of skin integrity within 9 d. In conclusion, AFL and NI result in distinct cutaneous biodistribution patterns and pharmacokinetic profiles for BLM applied to in vivo skin. Evaluation of LSRs showed that both methods were similarly tolerable, and each method has potential for individualized approaches in a clinical setting.